2011
DOI: 10.1007/s10661-011-2323-0
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation pattern of flubendiamide in/on brinjal (Solanum melongena L.)

Abstract: Residues of flubendiamide and desiodo flubendiamide were studied following three applications of flubendiamide 480 SC at 7 days interval at 90 and 180 g a.i. ha(-1) in/on brinjal fruits. An average initial deposit of 0.33 and 0.61 mg kg(-1) of flubendiamide was observed respectively after application at single and double dosages. The residues of flubendiamide dissipated quickly at both the dosages, and after 3 days, the extent of dissipation was found to be about 76% and 79% at the single and double dosages, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…The contradictory observation with Ca 2+ is its ability to stimulate ATP synthesis and mitochondrial dysfunction as a result of loss of cellular Ca 2+ homeostasis (O‐Uchi et al., ). Flubendiamide also has larvicidal action as a stomach poison and an oral intoxicant (Takkar, Sahoo, Singh, Battu, & Singh, ). Insecticides interfering with mitochondrial respiration induce generation of ROS such as free radicals (FR), hydrogen peroxides (H 2 O 2 ) and peroxynitrite anions which interact with the cellular organic matters such as membranes, lipids and proteins, and nucleic acids leading to the oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…The contradictory observation with Ca 2+ is its ability to stimulate ATP synthesis and mitochondrial dysfunction as a result of loss of cellular Ca 2+ homeostasis (O‐Uchi et al., ). Flubendiamide also has larvicidal action as a stomach poison and an oral intoxicant (Takkar, Sahoo, Singh, Battu, & Singh, ). Insecticides interfering with mitochondrial respiration induce generation of ROS such as free radicals (FR), hydrogen peroxides (H 2 O 2 ) and peroxynitrite anions which interact with the cellular organic matters such as membranes, lipids and proteins, and nucleic acids leading to the oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…Takkaret al (2011) [13] also reported the residues of flubendiamide 480 SC on brinjal fruits at 90 and 180 g a.i.ha -1 and observed that the initial deposit of 0.33 and 0.61 mg kg -1 , dissipated by 76.00 and 79.00 per cent after 3 rd day of application and half life ranged from 0.62 days and 0.54 days, at single and double doses, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Mohapatra et al (2010) reported 3.9 and 4.45-day half-life values of flubendiamide on cabbage following application of flubendiamide at 24 and 48 g a.i.ha −1 . The half-life values of flubendiamide on brinjal were observed to be 0.62 and 0.54 days, respectively, following three applications of flubendiamide 480 SC at 90 and 180 g a.i.ha −1 on brinjal fruits (Takkar et al 2012). Similarly, the half-lives of flubendiamide were reported to be 2.68 and 2.55 days following application of flubendiamide at 90 and 180 g a.i.ha −1 on brinjal fruits (Chawla et al 2011).…”
Section: Persistence Of Flubendiamide On Tomato Fruitsmentioning
confidence: 91%
“…As with the other insecticides, the residues of flubendiamide on tomato declined with time, and a fairly high rate of dissipation was observed. These Takkar et al (2012) who studied the residues of flubendiamide and desiodo flubendiamide following three applications at 90 and 180 g a.i. ha −1 on brinjal fruits and reported an average initial deposit of 0.33 and 0.61 mg kg −1 , respectively, at single and double dosages.…”
Section: Persistence Of Flubendiamide On Tomato Fruitsmentioning
confidence: 99%